A descriptive analysis of IT adoption in Malaysian small software firms - Mohamed, Norshidah; Hussein, Ramlah; Ahlan, Abdul Rahman; Hazza, Zubaidah Muataz (IEEE, 2009)
This paper reports the progress of a research that focuses on information technology (IT) adoption in Malaysian small software firms. The research provides insights into the characteristics of small software firms and the types of technology adopted in such firms.